The Hidden Power of Smell How Chemicals Influence Our Lives and Behavior - Moore, Paul A. (Springer International Publishing : Imprint: Springer, 2016)
This book provides insight into an area that humans often take for granted. There are wonderful and exciting stories of organisms using chemical signals as a basis of a sophisticated communication system. In many instances, chemical signals can provide more detailed and accurate information than any other mode of communication, yet this world is hidden from us because of our focus on visual and auditory signals.